EMPLOYEE COMMITMENT, QUALITY MANAGEMENT, AND TECHNOLOGY: EFFECTS ON PERFORMANCE AND SUSTAINABILITY - Saputra, Muhamad Ferdian; Arifin, Andi Harmoko; Hamzah, Muhammad Nasir; Rahim, Abdul Rahman (Jurnal Manajemen dan Bisnis, 2025)
This study examines the influence of Employee Commitment (EC), Quality Management (QM), and Technological Proficiency (TP) on Employee Performance (EP) and Organizational Sustainability (OS) at the Central Bureau of Statistics (BPS) of West Sulawesi Province, using Partial Least Squares Structural Equation Modeling (PLS-SEM). The data analysis reveals that the measurement model (outer model) meets the validity and reliability criteria, with Cronbach’s Alpha and Composite Reliability values exceeding 0.7 and AVE 0.5. In the structural model (inner model), EC, QM, and TP have a significant positive influence on EP, with p-values of 0.005, 0.026, and 0.022, respectively. However, EP does not significantly affect OS (p value = 0.795) and fails to serve as an effective mediator between the three exogenous variables and OS. Meanwhile, EC has a direct and significant impact on OS (p value = 0.024). The R² values for EP (41.7%) and OS (52.9%) indicate a moderate to strong predictive power of the model. The case study at BPS West Sulawesi Province demonstrates that while improvements in technological competency and quality management enhance employee performance, their effect on organizational sustainability remains limited. These findings highlight the critical role of strengthening employee commitment as a primary strategy for achieving long-term organizational sustainability. Practical implications of this study include the need for policies focused on enhancing EC and reassessing the mechanisms through which EP influences OS. For future research, incorporating additional mediating or moderating variables is recommended to deepen the understanding of the dynamic relationships between these factors in public sector organizations.